Community Structure of Rhopalocera Butterflies in The Sendang Gile Waterfall Area, North Lombok - Zaitun, Nurrifta; Ilhamdi, Mohammad Liwa; Artayasa, I Putu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Butterflies of the suborder Rhopalocera play an important ecological role as pollinators and bioindicators of environmental quality. The Sendang Gile Waterfall area, North Lombok, contains diverse habitats that potentially support a high diversity of butterfly species, yet information on their community structure remains limited. This study aimed to identify the species composition and analyze the community structure of Rhopalocera butterflies in the area. The research was conducted from April to May 2026 at four observation sites using a survey method. Butterflies were collected using sweep nets and identified based on morphological characteristics. Community structure was analyzed using the Shannon–Wiener diversity index (H′), Pielou evenness index (E), and Simpson dominance index (D). A total of 1,207 individuals representing 31 species from six families were recorded. Pieridae was the most abundant family, followed by Nymphalidae and Papilionidae, whereas Riodinidae, Lycaenidae, and Hesperiidae were represented by relatively few individuals. The waterfall site showed the highest diversity (H′ = 2.73) and evenness (E = 0.91), while Gate 1 had the lowest diversity (H′ = 2.10) and evenness (E = 0.67). Dominance values at all observation sites were low (D < 0.5). These results indicate that the Rhopalocera butterfly community in the Sendang Gile Waterfall area is relatively stable, with moderate to high species diversity, high evenness, and low dominance.